Impact of variable titer COVID-19 convalescent plasma and recipient SARS-CoV2-specific humoral immunity on survival in hospitalized patients. - Carlo J Iasella; Stefanie J Hannan; Emily J Lyons; Sophia C Lieber; Antu Das; Dimiter Dimitrov; Wei Li; Melissa Saul; Iulia Popescu; Ritchie Koshy; Robin Burke; Braidon Lape; et al. (PLoS ONE)
COVID-19 convalescent plasma (CCP) was one of the first therapies to receive emergency use authorization for management of COVID-19. We assessed the effectiveness of CCP in a propensity-matched analysis, and whether the presence of antibodies in the recipient at the time of treatment or the titer of antibodies in the administered CCP influenced clinical effectiveness. In an inpatient population within a single large health system, a total of 290 CCP patients were matched to 290 controls. While CCP increased titers of anti-SARS-CoV-2 RBD IgG titers post-CCP (p = <0.0001), no differences in 30-day survival were observed between CCP patients and controls in univariate and multivariate analyses. Survival at 30 days was numerically lower in recipients who were seronegative prior to CCP administration, compared to those with low titer and high titer anti-SARS-CoV-2 RBD IgG, respectively, but did not reach statistical significance (56% vs 82% vs 75%, p = 0.16). Patients who received 2 units of high-titer CCP had numerically better survival versus those who received fewer high-titer units, but this was not statistically significant (p = 0.08). CCP did not improve 30-day survival compared to propensity matched controls. Together these data support that CCP therapy provides limited benefit to hospitalized patients with SARS-CoV-2 infection.